CTM121 : Set and props for the theatre and film / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2023)
Set and Props for Theatre and Film is a structured hands-on introduction to the understanding, crafting and execution of theatrical and film production. The emphasis of this course to learn the basics of theatre and film terminology and to obtain the hands-on skills to properly execute the basic theatre and film set/props production. This syllabus also explores the roles and responsibilities and its relation between art directors, master carpenter, scenic artist, stage crew, props master, and the other stage as well as production management team. Set and Props for Theatre and Film will also introduce the first semester technician to the areas of stagecraft and theatrical production process and technique, such as budgeting, tools/equipment, set construction, scene painting, stage/film properties, fly system and health and safety requirements. Students are encouraged to participate in all theatre productions as part of their practicum, task and assignment.